Implementation Of Augmented Reality Technology In Virtual Practicum Of High School Chemistry Subjects - Singh, Bodhisatva; Zhang , Jiazhen (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research aims to investigate the implementation and effectiveness of Augmented Reality (AR) technology in virtual practicum activities for high school chemistry subjects. The study is motivated by the limited availability of laboratory facilities in many schools, which often hampers students' practical understanding of abstract and complex chemical concepts. By integrating AR into the learning process, students are provided with an interactive and immersive experience that simulates real laboratory experiments without the need for physical equipment. The research adopts a quasi-experimental method with a control and experimental group. The participants were 60 students from two different high schools, selected through purposive sampling. The experimental group engaged in virtual practicum using an AR-based application developed for this study, while the control group followed conventional practicum procedures. Data collection techniques included pre-tests and post-tests to measure students' conceptual understanding, as well as questionnaires and interviews to capture their engagement and perceptions. The results showed a significant increase in the post-test scores of the experimental group compared to the control group, indicating that AR-based virtual practicum had a positive impact on students’ understanding of chemical reactions, molecular structures, and lab procedures. Additionally, students reported higher levels of motivation and interest, highlighting the immersive and visually rich environment provided by AR technology. In conclusion, the implementation of AR in virtual chemistry practicums presents a promising solution to address laboratory limitations while enhancing students’ comprehension and engagement. This research recommends further development and integration of AR tools in science education to support interactive and cost-effective learning.